Changes of Brain Endothelin Levels and Peripheral Endothelin Receptors by Chronic Cigarette Smoke in Spontaneously Hypertensive Rats - Norikazu Ohno; Takeshi Tanaka; Taizo Kita; Kaoru Kubo; Keiji Shimada; Yukio Yonetani; Noboru Konishi; Toshikatsu Nakashima (Elsevier, 2004)
The present study was conducted to evaluate the contribution of endothelin (ET) to the pharmacodynamic response to chronic cigarette smoke in spontaneously hypertensive rats (SHR). The contribution of ET was studied consequent to the hemodynamic response following 8 weeks of cigarette smoke by determining the changes in tissue ET-1 content and ET receptors. The blood pressure (BP) at the early phase of smoking and the heart rate (HR) 24 h later were apparently reduced in SHR, while the HR at the early phase was transiently elevated in normotensive Wistar Kyoto (WKY) rats. Tissue ET-1 levels in the hypothalamus, striatum, and cortex of SHR were higher than those in WKY rats, and these higher levels in SHR were reduced by exposure to chronic cigarette smoke. The ET-1 contents in the medulla oblongata and midbrain of both strains were clearly increased by smoke exposure, although the levels of SHR and WKY rats were not different. In addition, the immunoreactivity of the ET type A receptor in the adrenal glands and type B receptor in the kidneys of SHR showed a different response to smoke exposure as compared to WKY rats. Our present findings suggest that the changes of ETs may relate to the pharmacodynamic effects of chronic cigarette smoke. Keywords:: endothelin, spontaneously hypertensive rat, cigarette smoking, hypertension, endothelin receptor